SWAT-N2O coupler: An integration tool for soil N2O emission modeling. (May 2019) - Gao, Xiang; Ouyang, Wei; Hao, Zengchao; Xie, Xianhong; Lian, Zhongmin; Hao, Xin; Wang, Xuelei
Abstract: Nitrous oxide (N2 O) is one of the types of diffuse gaseous nitrogen lost mainly from agricultural soil, and it is a potent greenhouse gas contributing to climate warming. Both empirically based and process-based (e.g., Soil and Water Assessment Tool, SWAT) modeling methods for simulating N2 O emissions have been used, and each has its own advantages and disadvantages. We first developed an empirically based N2 O emission algorithm using 4488 individual measurements. By integrating the modified hydrological model for paddy fields, empirical N2 O models for non-paddy fields and paddy fields into SWAT's existing crop growth, hydrology, and nitrogen cycling algorithms, we then created new modeling tools (SWAT-N2 O coupler tools) that allow users to perform simulations of soil N2 O emissions for non-paddy fields and paddy fields at different temporal-spatial scales. Furthermore, our tools allow users to efficiently conduct a time-space analysis by using the spatio-temporal analysis module and the sensitivity analysis by using scenario analysis module. The developed tools were demonstrated in an agricultural watershed in northeast China. The model performance and temporal-spatial evaluation indicate that the SWAT-N2 O coupler tools would be an alternative and a useful way to capture the magnitudes and seasonal pattern of N2 O fluxes in non-paddy fields and paddy fields. A further sensitivity analysis indicates that N2 O emissions are sensitive to precipitation and applied N rate in paddy fields, moderately sensitive to precipitation in non-paddy fields as well as to air temperature in paddy fields, and relatively insensitive to the applied N rate and air temperature in non-paddy fields. The developed coupler tools could reliably depict how these factors interact and their effect on N2 O emissions or absorptions under different cropping systems. Highlights: Nitrous oxide fluxes are modeled with functional relationships between soil NO3 − -N, temperature and water content. The developed models can capture the magnitudes and seasonal pattern of N2 O fluxes well in soybean and paddy fields. The integrated model is particularly sensitive to precipitation and applied N rate in paddy fields. SWAT-N2 O coupler tools also provide spatio-temporal analysis module and scenario analysis module.